2013
DOI: 10.1155/2013/812641
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Ginseng against Alteration of Calcium Binding Proteins Immunoreactivity in the Mice Hippocampus after Radiofrequency Exposure

Abstract: Calcium binding proteins (CaBPs) such as calbindin D28-k, parvalbumin, and calretinin are able to bind Ca2+ with high affinity. Changes in Ca2+ concentrations via CaBPs can disturb Ca2+ homeostasis. Brain damage can be induced by the prolonged electromagnetic field (EMF) exposure with loss of interacellular Ca2+ balance. The present study investigated the radioprotective effect of ginseng in regard to CaBPs immunoreactivity (IR) in the hippocampus through immunohistochemistry after one-month exposure at 1.6 SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Helmholtz coils, consisting of two circular electromagnets placed along a common axis, were the preferred generator for ELF-EMFs (67% of papers), while the Wave Exposer V20 custom device (extensively described in Ref. 53) was the most common generator for RF-EMFs (43%), maybe by virtue of the multiple studies published by the same team. Other highly represented RF-EMF generators were the Coplanar Waveguide (CPW) (28.5%), consisting of a single conducting track printed onto a dielectric substrate and arranged to be in the middle of a pair of return conductors, and mobile phones (28.5%).…”
Section: Experimental Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Helmholtz coils, consisting of two circular electromagnets placed along a common axis, were the preferred generator for ELF-EMFs (67% of papers), while the Wave Exposer V20 custom device (extensively described in Ref. 53) was the most common generator for RF-EMFs (43%), maybe by virtue of the multiple studies published by the same team. Other highly represented RF-EMF generators were the Coplanar Waveguide (CPW) (28.5%), consisting of a single conducting track printed onto a dielectric substrate and arranged to be in the middle of a pair of return conductors, and mobile phones (28.5%).…”
Section: Experimental Platformsmentioning
confidence: 99%
“…Exposure to both acute and chronic ELF-EMFs promotes calcium influx, resulting in an increased intracellular calcium concentration in various types of neurons 39,40,52 that is conversely decreased following chronic exposure to RF-EMFs. 41,42,53 The involvement of calcium is remarkable because of the many related calcium signaling pathways involved in various essential neurophysiological processes, such as neural differentiation, survival, and apoptosis 54,55 that could ultimately explain the many effects of EMF exposure on learning and memory. 56 In areas of the brain involved in the modulation of these cognitive tasks, such as the hippocampus and prefrontal cortex, exposure to ELF-EMFs resulted in abnormal calcium signaling that led to a decrease in the binding between the N-methyl-d-aspartate receptor (NMDAR) and its ligand glutamate, which could directly result in important effects on synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis is a product of great interest, both in the field of medicine and the pharmaceutical industry with numerous properties including antioxidant, antieinflammatory, immune stimulant, hepatoprotector, and carcinostatic (Montoro et al, 2010;Viuda-Martos, Ruiz-Navajas, Fern andez-L opez, & P erezAlvarez, 2008). Therefore, we thought that trying this extract as a radio protective agent against ionizing radiation (IR) may prove beneficial effect (Maskey, Lee, Kim, & Kim, 2013). Since BC patients were exposed to IR, the genotoxic effects of IR were studied in white blood cells, which circulate throughout the body and which have been confirmed as a useful biodosimeters by many radiation studies (Lamkowski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Maskey et al (2013) have studied alterations on Ca +2 levels after radiofrequency exposure by measuring the immune reactivity of calcium-binding proteins (such as calbindin D28-k, parvalbumin and calretinin), and have observed immunohistochemical alterations on the CA1, CA3 and DG regions. Zou et al have reported that microwave radiation stimulated neuronal apoptosis depends on the caspase-3 pathway.…”
Section: Evaluation Of Cell Death and Pathwaysmentioning
confidence: 99%